2015
DOI: 10.1186/s12891-015-0538-x
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical evaluation of a new pedicle screw-based posterior dynamic stabilization device (Awesome Rod System) - a finite element analysis

Abstract: BackgroundPedicle-screw-based posterior dynamic stabilization devices are designed to alleviate the rate of accelerated degeneration of the vertebral level adjacent to the level of spinal fusion. A new pedicle- screw-based posterior dynamic stabilization device- the Awesome Dynamic Rod System was designed with curve cuts on the rods to provide flexibility. The current study was conducted to evaluate the biomechanical properties of this new device.MethodsFinite element models were developed for the intact spine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 31 publications
2
14
0
Order By: Relevance
“…Screw lengths were 45 mm. The thread on the pedicle screws was underestimated [29][30][31][32] to reduce the computational weight of the models. The 'tie' constraint was created between the pedicle screws and the vertebraes to be permanently bonded together by full constraint.…”
Section: Fe Model Creationmentioning
confidence: 99%
“…Screw lengths were 45 mm. The thread on the pedicle screws was underestimated [29][30][31][32] to reduce the computational weight of the models. The 'tie' constraint was created between the pedicle screws and the vertebraes to be permanently bonded together by full constraint.…”
Section: Fe Model Creationmentioning
confidence: 99%
“…e finite element (FE) modeling technique enables the exploration of different scenarios using computer models, and once validated, it can serve as an effective tool in biomechanics. erefore, in recent years, the FE technique has been widely used to investigate the biomechanical performance of different techniques [16][17][18][19][20][21][22], including analyzing different types of S1 screw fixation [22] and evaluating different fixation techniques for the treatment of sacroiliac joint injuries [18]. However, only a few studies have investigated the biomechanical stability of different fixation techniques for posterior pelvic ring fractures.…”
Section: Introductionmentioning
confidence: 99%
“…Dynamic stabilization (DS) devices are mostly preferred in the cases of minor degeneracy in order to preserve motion and to improve physiological load transmission so as to relieve pain. [5][6][7][8][9] Spinal fusion having rigid instrumentation accelerates the degeneracy of adjacent FSUs, stress concentration and morbidity complications. [10][11][12][13] The clinical efficacy and the biomechanical aspects of such implants are to be evaluated through long-term follow-up observational study, in vitro/in vivo experiments and numerical simulations.…”
Section: Introductionmentioning
confidence: 99%
“…It was mentioned that Dynesys behaved stiffer as compared to TOPS system and better load sharing was observed at reduced load resulting in minimization of screw loosening at bone-screw interface. Chen et al 9 have performed biomechanical study of a new posterior DS device named ''Awesome Rod System (AWE)'' located at L4-L5 considering a FE model of lumbar segment (L1-L5). Authors concluded that AWE shields the fusion segments with increase in ROM, facet contact forces and disc stresses at the adjacent level of instrumented segments.…”
Section: Introductionmentioning
confidence: 99%